Acoustic phonon tunneling in LiNbO3 - Hakanen, Toivo (2024)
In this thesis, the patterning techniques of lithium-niobate-on-insulator silicon chips were investigated to create free-standing membrane platforms of LiNbO3 (lithium niobate) that are separated by a submicron gap for cryogenic acoustic phonon tunneling measurements. A three-layer mask of mr-PosEBR - Al2O3 - Cr was utilized in LiNbO3 dry etching to achieve good gap edge quality. An estimated Cr to LiNbO3 selectivity of 0.3 was achieved with an estimated LiNbO3 etch rate of 6 nm/min and edge wall verticality of 56°. HF vapor was used to etch SiO2 from underneath LiNbO3 and release membrane platforms from bulk, and evaporated Al2O3 was used to protect devices from unwanted corrosion. Vapor etch had a SiO2 etch rate of 0.5 µm/min, which is much higher than values found in literature. Ultimately, sample fabrication failed because the Al2O3 coating on top of membranes didn’t protect the measurement devices fabricated on top of LiNbO3 platforms from HF corrosion. Numerical calculations showed that the heat flux from the acoustic phonon tunneling is the strongest in the crystallographic X-direction, with a value of 5.2 µW/m2 for two semi-infinite plates separated by a 200 nm gap at 0.1 K. Heat fluxes in the Yand Z-directions were 5.0 µW/m2 and 2.1 µW/m2 , respectively, under the same conditions. A similar trend was observed with tunneled power transmittance in the Y- and Z-directions: the Y-direction had higher power transmittance across all incident mode-tunneled mode pairs compared to the Z-direction.